2010
DOI: 10.1021/jf102847p
|View full text |Cite
|
Sign up to set email alerts
|

Response of Glucosinolate and Flavonoid Contents and Composition of Brassica rapa ssp. chinensis (L.) Hanelt to Silica Formulations Used as Insecticides

Abstract: Silica-based substances have increased in popularity in recent years as alternative insecticides in horticultural crop protection. However, no research has been conducted into the influence of silica on plant biochemistry. Formulations (Fossil Shield 90.0s, AE R974, AL-06-109, Surround) were applied electrostatically on pak choi. Plants were harvested on two dates to measure immediate (first) and decelerated (second) influence, as well as recovery following the removal of silica formulations. The predominant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…It has already been reported that B. rapa subspecies chinensis produces lot of kaemferol and isorhamnetin type flavonoids. 11 These flavonoids have the potentials to act as both analgesic 36,37 and antidepressant agents. 38,39 These might be considered as one of the reasons to justify the analgesic and antidepressant actions of this herb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been reported that B. rapa subspecies chinensis produces lot of kaemferol and isorhamnetin type flavonoids. 11 These flavonoids have the potentials to act as both analgesic 36,37 and antidepressant agents. 38,39 These might be considered as one of the reasons to justify the analgesic and antidepressant actions of this herb.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Previous chemical studies of Brassica genus reported the isolation of phenolics and organic acids. [10][11][12][13] As a part of our continuing studies on medicinal plants of Bangladesh, [14][15][16][17][18] our aim was to screen B. rapa subspecies chinensis for primary analgesic and antidepressant activities. This is the first time report regarding these bioassays of this plant and it might be useful for inspiring bioactivity guided isolation of compounds from this herb.…”
Section: Brassica Rapa Subsp Chinensis (Bengali Namementioning
confidence: 99%
“…Extraction and analysis of GS were performed as described previously by Mucha-Pelzer et al (2010) (Mucha-Pelzer et al 2010). Briefly, freeze-dried 20-to 30-mg samples were extracted with 70% methanol at 80°C, and the resulting GS-containing extracts were applied on a Sephadex DEAE A25 anion-exchange column (Sigma-Aldrich, Israel); after several equilibration steps and overnight incubation with sulfatase, desulfo-GS were eluted with 1-mL aliquots of water, and the GS were separated and measured with an HPLC ProStar 240 high-performance liquid chromatography (Varian, Palo Alto, CA) equipped with an Acclaim reverse-phase C18 column (2.1 9 250 mm, 5 lm) (Dionex, Sunnyvale, CA).…”
Section: Glucosinolates Extraction and Hplc Analysismentioning
confidence: 99%
“…This plant is popular for providing nutrients, vitamins and minerals (Dominguez-Perles et al 2014, Siddiqui et al 2014. Previous phytochemical studies of Brassica genus reported the isolation of some phenolics and organic acids (Fernandes et al 2007, Mucha-Pelzer et al 2010, Tenore et al 2012.…”
mentioning
confidence: 99%